The impact of the precautionary measures taken in the kingdom of Bahrain to contain the outbreak of COVID-19. Issue 1 (1st January 2021) - AlSayegh, Mona Abdul Karim; Iqbal, Azhar
Abstract: As a worldwide pandemic is unavoidable, its spread must be observed to reduce and contain it. The Kingdom of Bahrain sought to implement the World Health Organization (WHO) directives to take precautionary measures and appropriate preventive steps to limit the spread of the coronavirus among people and developed an integrated plan to contain it. This study purposes to investigate the effect of precautionary and preventive measures in limiting the spread of coronavirus in Bahrain. Statistics and the details of precautionary measures described in this study are obtained from websites maintained by the Ministry of Health (MOH) in Bahrain. The calculated number of infected and death cases is determined by using polynomial functions that fit the data. The outcomes obtained showed that the number of cumulative infected and death cases were less than the expected numbers except for certain periods. Reopening stores and businesses that provide direct services to people after their two-week closing resulted in a 36% increased in infected cases than expected in the closing period. When the lockdown continued, the number of infected people dropped to 64% of the total number of detected infections. In accordance with our results, it is expected that the number of infected cases will gradually decrease till late March 2021. With continuing lockdown and their compliance in implementing the precautionary measures with consciousness, it is anticipated that Bahrain will soon be in the final state of the epidemic.